DEFINING MORE INCLUSIVE SOCIAL POLICIES FOR PEOPLE WITH DISABILITIES - Vazquez, Debora (Critical Disability Discourses, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Social policies in Canada are presently nurtured by a neo-liberal view such that they address limitations of underprivileged groups by providing incentives or solutions at the individual level. These policies have failed to effect structural change that would recognize the need to promote the full inclusion of these groups, particularly people with disabilities. This neo-liberal view is based on a deficiency model that perpetuates a situation of prejudice and discrimination against this vulnerable group. Members of marginalized groups require policies and supports that promote equality and inclusion in their communities. A deep structural transformation must include the removal of prejudices, barriers, and segregation that limit the full potential of people with disabilities.